Epidemiology of yeast species causing bloodstream infection in Tehran, Iran (2015‐2017); superiority of 21‐plex PCR over the Vitek 2 system for yeast identification. Issue 5 (May 2020) - Kord, Mohammad; Salehi, Mohammadreza; Khodavaisy, Sadegh; Hashemi, Seyed Jamal; Daie Ghazvini, Roshanak; Rezaei, Sassan; Maleki, Ayda; Elmimoghaddam, Ahmad; Alijani, Neda; Abdollahi, Alireza; Doomanlou, Mahsa; Ahmadikia, Kazem; et al.
Abstract : Introduction. : Given the limited number of candidaemia studies in Iran, the profile of yeast species causing bloodstream infections (BSIs), especially in adults, remains limited. Although biochemical assays are widely used in developing countries, they produce erroneous results, especially for rare yeast species. Aim. : We aimed to assess the profile of yeast species causing BSIs and to compare the accuracy of the Vitek 2 system and 21‐plex PCR. Methodology. : Yeast blood isolates were retrospectively collected from patients recruited from two tertiary care training hospitals in Tehran from 2015 to 2017. Relevant clinical data were mined. Identification was performed by automated Vitek 2, 21‐plex PCR and sequencing of the internal transcribed spacer region (ITS1‐5.8S‐ITS2). Results. : In total, 137 yeast isolates were recovered from 107 patients. The overall all‐cause 30‐day mortality rate was 47.7 %. Fluconazole was the most widely used systemic antifungal. Candida albicans (58/137, 42.3 %), Candida glabrata (30/137, 21.9 %), Candida parapsilosis sensu stricto (23/137, 16.8 %), Candida tropicalis (10/137, 7.3 %) and Pichia kudriavzevii ( Candida krusei ) (4/137, 2.9 %) constituted almost 90 % of the isolates and 10 % of the species detected were rare yeast species (12/137; 8.7 %). The 21‐plex PCR method correctly identified 97.1 % of the isolates, a higher percentage than the Vitek 2 showed (87.6 %). Conclusion. : C. albicans was the main cause of yeast‐derived fungaemia in this study. Future prospective studies are warranted to closely monitor the epidemiological landscape of yeast species causing BSIs in Iran. The superiority of 21‐plex PCR over automated Vitek 2 indicates its potential clinical utility as an alternative identification tool use in developing countries.